DESKRIPSI KONSEP PERKALIAN SEBAGAI PENJUMLAHAN BERULANG - Kulimbang, Elieser; Maniboey , Lidwina C; Rian Efendi (Almeera Education, 2025)
This study aims to examine the understanding of multiplication as repeated addition among fifth-grade elementary school students in solving multiplication problems. This research is a qualitative descriptive study, as the researcher seeks to describe how students solve problems related to the concept of multiplication operations. The subjects of this study were three fifth-grade students from State Elementary School 2 Abepura, Jayapura City, selected to represent different types or groups of problem-solving approaches related to multiplication operations. The subjects were chosen using purposive sampling, which involves selecting participants based on specific criteria or purposes. The research instruments consisted of a test sheet containing essay questions on multiplication and a flexible interview guide. Data were analyzed through three stages: data reduction, data presentation, and conclusion drawing. The results showed that all three subjects did not understand the concept of multiplication as repeated addition; instead, they relied solely on memorizing multiplication facts.